2001
DOI: 10.1159/000048716
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factor Control of CNS Myelination

Abstract: The molecular signals required for initiating myelination and maintenance of the myelin internode are not known. Several growth factor families have been implicated in promoting oligodendrocyte survival or differentiation and may have consequences on formation of myelin. We developed a reliable assay for detecting ensheathment of neurites by oligodendrocytes in spinal cord explants. This system was used to assay the effect of selected growth factors on myelin internode formation. We examined the influence on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 77 publications
3
28
0
Order By: Relevance
“…The level of Nrg-1 type III expressed on the surface of the axon in the PNS has been shown to regulate both whether an axon is myelinated and the thickness of the sheath (Michailov et al, 2004;Taveggia et al, 2005), confirming a central role for Nrg in PNS myelination. Our results, and those of Park et al (2001) using spinal cord explants, show clearly that oligodendrocyte myelination in vitro is enhanced by exogenous Nrg1. Furthermore, our observation that Nrg-blocking antibodies or ErbB4/Fc chimeras can inhibit myelination to a level below that seen in control cultures suggests that endogenous Nrg1 generated in these cultures also contributes to myelination.…”
Section: Discussionsupporting
confidence: 79%
“…The level of Nrg-1 type III expressed on the surface of the axon in the PNS has been shown to regulate both whether an axon is myelinated and the thickness of the sheath (Michailov et al, 2004;Taveggia et al, 2005), confirming a central role for Nrg in PNS myelination. Our results, and those of Park et al (2001) using spinal cord explants, show clearly that oligodendrocyte myelination in vitro is enhanced by exogenous Nrg1. Furthermore, our observation that Nrg-blocking antibodies or ErbB4/Fc chimeras can inhibit myelination to a level below that seen in control cultures suggests that endogenous Nrg1 generated in these cultures also contributes to myelination.…”
Section: Discussionsupporting
confidence: 79%
“…PDGF is a major mitogen and stimulant of motility of mesenchymal cells and its isoforms act via two receptor tyrosine kinases, PDGF receptors a and b. Research has shown that PDGF is related to the neuronal trophic activity of the CNS in both embryonic and postnatal phases [25][26][27][28][29]. Also, PDGF might promote functional recovery after spinal cord injury and sciatic nerve injury [30][31][32], indicating its potential role in early neuroplasticity following injury.…”
Section: Introductionmentioning
confidence: 99%
“…Oligodendroglial differentiation can be also enhanced using PDGFa, which promotes their survival (Gogate et al, 1994) in collaboration with NT3 and Triiodothyronine (T3), factors necessary for the correct development of oligodendrocytes and the expression of myelin proteins (Billon et al, 2002;Park et al, 2001). …”
Section: Differentiationmentioning
confidence: 99%